Effects of soil heterogeneity on the nonlinear response of highway bridges and conditionally simulated spatial variable movements - Nadjib HEMAIDI ZOURGUI; Rachid BAKHTI; Abdelghani LAIB; Baizid BENAHMED (Electronic Journal of Structural Engineering, 2025)
This paper investigates the soil lateral heterogeneity effects, particularly the loss of the coherence induced by soil lateral heterogeneity effects as the excitation frequencies increase past the mean dominant frequency of the soil profile, on the conditionally simulated spatially variable ground motions and the nonlinear dynamic behavior of highway bridges. Spatially variable seismic ground motions are conditionally generated according to the coherency model of Laib and al. (Earthq Eng & Eng Vib 2015) using the simulation algorithm of Vanmarcke et al. (Journal of Engineering Mechanics 1993). The simulated time histories are then used to analyses the nonlinear dynamic behavior of a three spans continuous deck concrete bridge subjected to differential and identical support seismic ground motions. The results indicate as the coefficient of variation (CV) increases, the power spectral density of simulated time histories increases too. The comparison of the pseudo-acceleration response spectra of target acceleration and that of simulated ones reveals that spectral values of simulated motions are 1.6 times greater than those of the reference motion in the vicinity of the mean predominant soil frequency because they are influenced by the site effects. This influence is obvious in the pseudo-velocity response spectra where the pseudo-velocity values are 2 times greater than those of reference motion in the vicinity of the mean resonant soil frequency for a relatively low value in CV (10%). The analysis of the bridge’s response indicates that the loss of coherence induced soil lateral heterogeneity effects as the frequencies increase beyond the mean predominant frequency of the site has a great influence on the dynamic response of the studied bridge and cannot be neglected, despite the relatively short length of the studied bridge and its foundation on firm soil. It is found that soil heterogeneity induces an increase of 50% in the relative displacements of pier 2 of the studied bridge. This influence can be more significant for long bridges founded on soft soil type.